Isolasi dan Karakterisasi Senyawa Triterpenoid dari Ekstrak Etil Asetat Daun Mengkudu (Morinda Citrifolia L.) - Ferdinal, Norman; Fitri Khairuni; Suryati (Departemen Kimia Universitas Andalas, 2025)
Morinda citrifolia L., commonly known as the Noni plant, is a plants from the Rubiaceae family that can be found in Indonesia has various benefits. Traditionally, noni is often used as a cough medicine, flu, pain, hypertension, malaria, anthelmintic, and diarrhea. The purpose of this study is to isolate and characterize triterpenoid compounds from ethyl acetate extract of noni leaves. The isolation process was carried out by liquid vacuum chromatography and column chromatography. The compound was obtained in the form of white solids as much as 0,0038 g with a melting point of 233 – 235 oC. This compound identified on the TLC plate using the Liebermann-Burchard (LB) reagent which produced a single purple spot. The results of UV spectrophotometry characterization obtained a spectrum with λmax = 292 nm, indicating an n→π* electron transition. The IR spectrum shows the presence of the O-H functional group at a wavelength of 3853,94 cm-1, 3742,55 cm-1 and 3613,18 cm-1. the C-H functional group at wave number 2922,32 cm-1, the C=O functional group at wave number 1690,13 cm-1 and the C-O group at wave numbers 1033,12 cm-1. The absorption of the geminal dimethyl group, which is characteristic of triterpenoid compounds at 1454,77cm-1 dan 1376,97 cm-1.